A web demo for the Data Encryption Standard (DES) - Tan, Xuan Wei (2017)
With the rapid advancement of technology, data security has become a much more important factor to consider in the development of software applications. Therefore, by understanding the basic architecture of DES and its encryption process which includes Feistel Cipher (a symmetric structure to construct block cipher), students of cryptography would be able to apply the concept of data encryption into their course assignments or future projects that requires data security. This project aims to deliver a web demo simulator to visualize all the intermediate and main steps in the encryption process of DES. This web demo simulator includes the steps to generate round keys for use in the encryption process. The web demo simulator will eventually serve as an accompanying learning material for students of cryptography. The objective of this report is to record the planning and development process of the web demo simulator. It will also be presented as a guide and further explanation on the web demo simulator, so that it will be more clear and beneficial for students learning about DES.